The influence of impact force redistribution and redirection on maximum principal strain for helmeted head impacts. Issue 13 (3rd October 2019) - Taylor, Karen; Hoshizaki, T. Blaine; Gilchrist, Michael
Abstract: Sporting helmets with linear attenuating strategies are proficient at reducing the risk of traumatic brain injury. However, the continued high incidence of concussion in American football, has led researchers to investigate novel helmet liner strategies. These strategies typically supplement existing technologies by adding or integrating head-helmet decoupling mechanisms. Decoupling strategies aim to redirect or redistribute impact force around the head, reducing impact energy transferred to the brain. This results in decreased brain tissue strain, which is beneficial in injury risk reduction due to the link between tissue strain and concussive injury. The purpose of this study was to mathematically demonstrate the effect of ten cases, representing theoretical redirection and redistribution helmet liner strategies, on brain tissue strain resulting from impacts to the head. The kinematic response data from twenty head impacts collected in the laboratory was mathematically modified to represent the altered response of the ten different cases and used as input parameters to determine the effect on maximum principal strain (MPS) values, calculated using finite element modeling. The results showed that a reduced dominant coordinate component (contributes the greatest to resultant) of rotational acceleration decreased maximum principal strain in American football helmets. The study theoretically demonstrates that liner strategies, if applied correctly, can influence brain motion, reduce brain tissue strain, and could decrease injury risk in an American football helmet.